2019
DOI: 10.1016/j.jmmm.2019.165384
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic magnetism in monolayer transition metal trihalides: A comparative study

Abstract: Two dimensional magnetic materials, with tunable electronic properties could lead to new spintronic, magnetic and magneto-optic applications. Here, we explore intrinsic magnetic ordering in two dimensional monolayers of transition metal tri-halides (MX 3 , M = V, Cr, Mn, Fe and Ni, and X = F, Cl, Br and I), using density functional theory. We find that other than FeX 3 family which has an anti-ferromagnetic ground state, rest of the trihalides are ferromagnetic. Amongst these the VX 3 and NiX 3 family are foun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 57 publications
(62 reference statements)
4
21
1
Order By: Relevance
“…The calculated geometric parameters and magnetic properties are summarized in Table 1 and Table S1. It can be clearly seen that lattice parameter increases from CrCl3, CrBr3 to CrI3, which is in accordance with previous reports [15,28,29]. The calculated band structure ( Fig.…”
Section: Magnetic Anisotropies and Exchange Interactions Of Crx3 MLsupporting
confidence: 91%
“…The calculated geometric parameters and magnetic properties are summarized in Table 1 and Table S1. It can be clearly seen that lattice parameter increases from CrCl3, CrBr3 to CrI3, which is in accordance with previous reports [15,28,29]. The calculated band structure ( Fig.…”
Section: Magnetic Anisotropies and Exchange Interactions Of Crx3 MLsupporting
confidence: 91%
“…Ce 2 Se 2 Br 4 , Nb 2 S 4 Cl 2 , ScTiCl 6¸C eNdBr 6 , NdTbBr 6 , and PrNdCl 6 had a metal trihalide-like structure, with the former three adopting a BiI 3 -like trigonal structure and the latter three adopting an NdBr 3like orthorhombic structure. Earlier reports have shown that metal trihalides depicted interesting magnetic behavior and could potentially be used in magnetic and spintronic applications (McGuire, 2017;Tomar et al, 2019). Thus, in addition to photocatalysts, these newly generated materials could be studied for other interesting applications as well.…”
Section: Generation Of Novel 2d Materialsmentioning
confidence: 99%
“…The ferromagnetic ground state can be identified by non-zero total magnetic moment per unit cell, which originates primarily from Ni atom. Based on calculated value of magnetic moment, Ni 3+ is found to exist in low spin state (1 µ B ) [16] ), DP constant (E l ), carrier mobility (µ), and relaxation time (τ) at the room temperature in both spin channels of NiCl 3 monolayer. The electronic properties of NiCl The effective mass (m * ij ) in the vicinity of Fermi level, a crucial parameter for the transport behavior of semiconductor, can be extracted from using the existing band structure.…”
Section: Crystal and Electronic Structuresmentioning
confidence: 99%
“…Several transition metal halide monolayers have been successfully prepared experimentally and their magnetism have been reported [2][3][4]. Some transition metal halide monolayers have been theoretically predicted to have ferromagnetic or anti-ferromagnetic ground states [5][6][7][8][9][10][11][12][13][14][15][16][17]. Among them, Ni-bases trihalides is theoretically predicted to be Dirac spin-gapless semiconductor with the Curie temperature above room temperatures [10,16,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation